PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN TEKSTIL DAN GARMEN - Silviani, Silviani (Media Akuntansi dan Perpajakan Indonesia, 2021)
In facing the intense business competition in the era of globalization, companies are required to be able to determine the right strategy for innovation. The role of intellectual capital is very important for companies in achieving competitive advantage as well as improving the financial performance. This study is aimed at examining the effect of the Intellectual Capital component on financial performance. The data used in this secondary data type of research are the financial reports of textile and garment companies starting from 2014 to 2019. The research method in this study using SPSS 25 application assistance. The results reveal that Capital Employed Efficiency (VACA) and Human Capital Efficiency (VAHU) do not give significant effect to Return On Asset, meanwhile, Structural Capital Efficiency (STAVA) has a positive effect to Return On Asset.